Resistance Through the Pen: A Critical Analysis of the Role of Prijaji Field in the National Movement (1907-1914) - Hasan Mukhlis; Arif Saefudin (Tarikhuna: Journal of History and History Education, 2024)
This research aims to examine the role of Medan Prijaji, a newspaper founded by Tirto Adhi Soerjo in 1907, in the anti-colonial movement during the period 1907-1914. The research method used is descriptive qualitative with a critical historical approach through literature study. The research results show that Medan Prijaji not only functions as a medium of information but also as a symbolic public space that enables socio-political mobilization. This newspaper became a catalyst in voicing criticism against colonialism and building community solidarity to achieve social change. These findings also highlight the importance of Medan Prijaji as a cultural resistance tool in facing cultural homogenization due to colonial domination. This research makes an important contribution to the study of socio-political history, particularly regarding the role of media in building resistance and solidarity. Moreover, these findings are relevant for understanding the potential of modern media as a tool of resistance in the current context of globalization.